Novel host‐specific iron acquisition system in the zoonotic pathogen Vibrio vulnificus. (4th March 2015) - Pajuelo, David; Lee, Chung‐Te; Roig, Francisco J.; Hor, Lien‐I.; Amaro, Carmen
Summary V ibrio vulnificus is a marine bacterium associated with human and fish (mainly farmed eels) diseases globally known as vibriosis. The ability to infect and overcome eel innate immunity relies on a virulence plasmid (pVvbt2) specific for biotype 2 (Bt2) strains. In the present study, we demonstrated that pVvbt2 encodes a host‐specific iron acquisition system that depends on an outer membrane receptor for eel transferrin called Vep20. The inactivation of vep20 did not affect either bacterial growth in human plasma or virulence for mice, while bacterial growth in eel blood/plasma was abolished and virulence for eels was significantly impaired. Furthermore, vep20 is an iron‐regulated gene overexpressed in eel blood during artificially induced vibriosis both in vitro and in vivo. Interestingly, homologues to vep20 were identified in the transferable plasmids of two fish pathogen species of broad‐host range, Vibrio harveyi (pVh1) and Photobacterium damselae subsp. damselae (pPHDD1). These data suggest that Vep20 belongs to a new family of plasmid‐encoded fish‐specific transferrin receptors, and the acquisition of these plasmids through horizontal gene transfer is likely positively selected in the fish‐farming environment. Moreover, we propose Ftbp (fish transferrin binding proteins) as a formal name for this family of proteins.